152k views
1 vote
-3x-3y=3 y=-5x-17

I m confused. Helppp

User Iateadonut
by
5.0k points

1 Answer

6 votes

So for this system I will be applying the substitution method. Since y = -5x - 17, replace the y variable in the first equation with -5x - 17 and solve for x as such:


-3x-3(-5x-17)=3\\-3x+15x+51=3\\12x+51=3\\12x=-48\\x=-4

Now that we have the value for x, substitute it into either equation to solve for y:


-3*-4-3y=3\\12-3y=3\\-3y=-9\\y=3\\\\y=-5*-4-17\\y=20-17\\y=3

In short, x = -4 and y = 3.

User SpokaneDude
by
5.3k points